Analysis of Organizational Culture, Motivation, Work Environment on Employee Performance at the Medan City DPRD Secretariat - Lubis, Harun; Nainggolan, Yolanda Jesika Margaretha Br.; Siregar, Erpian Richad Halomoan; Randolph, Yehezkiel Miquel; Novita, Herlina (Lembaga Riset Ilmiah, 2024)
The Medan City DPRD Secretariat is one of the agencies tasked with carrying out secretarial and financial administration as well as providing services to the leadership and members of the Medan City DPRD. The aim of this research is to analyze organizational culture, motivation and work environment on employee performance at the Medan City DPRD Secretariat office. This research uses a quantitative approach. The population in this research is all employees of the State Civil Apparatus at the Medan City DPRD Secretariat, numbering 50 people. The technique used in sampling is the saturation side technique, where the entire population is used as the research sample. Data sources were obtained from primary data through field research, namely interviews and distributing questionnaires to all employees at the Medan City DPRD Secretariat. Secondary data comes from journals and articles that are relevant to the problems that occur. Simultaneously, organizational culture (X1), work motivation (X2), work environment (X3) have a significant effect on employee performance (Y) at the Medan City DPRD Secretariat. Determination shows a result of 0.728, meaning that organizational culture, motivation, work environment contribute to employee performance at the Medan City DPRD Secretariat by 72.8%